From by-products to new application opportunities: the enhancement of the leaves deriving from the fruit plants for new potential healthy products - Regolo, Lucia; Giampieri, Francesca; Battino, Maurizio; Armas Diaz, Yasmany; Mezzetti, Bruno; Elexpuru-Zabaleta, Maria; Mazas, Cristina; Tutusaus, Kilian; Mazzoni, Luca (Frontiers in Nutrition, 2024)
In the last decades, the world population has grown exponentially, as well as the demand for any kind of productand demand for any kind of product has grown exponentially. The rhythm of production to satisfy the request of the population has become unsustainable and the concept of the linear economy, introduced after the industrial revolutionIndustrial Revolution, has been replaced by a new economic approach, the circular economy. In this new economic model, the concept of "the end of life" is substituted by the concept of restoration, providing a new life to many industrial wastes. Leaves are a by-product of several agricultural cultivations. In recent years, the scientific interest regarding leaf biochemical composition grew, recording that plant leaves may be considered an alternative source of bioactive substances. Plant leaves' main bioactive compounds are similar to those in fruits, i.e., phenolic acids and esters, flavonols, anthocyanins, and procyanidins. Bioactive compounds can positively influence human health; in fact, it is no coincidence that the leaves were used by our ancestors as a natural remedy for various pathological conditions. Therefore, leaves can be exploited to manufacture many products in the food (e.g., being incorporated in food formulations as natural antioxidants, or used to create edible coatings or films for food packaging), cosmetic and pharmaceutical industries (e.g. promising ingredients in anti-aging cosmetics such as oils, serums, dermatological creams, bath gels, and other products). This review focuses on the leaves' main bioactive compounds and their beneficial health effects, indicating their applications until today to enhance them leaves as a harvesting by-product and highlight their potential possible beneficial effectsreuse for new potential healthy products.